2017
DOI: 10.1186/s13321-016-0187-6
|View full text |Cite
|
Sign up to set email alerts
|

A novel descriptor based on atom-pair properties

Abstract: BackgroundMolecular descriptors have been widely used to predict biological activities and physicochemical properties or to analyze chemical libraries on the basis of similarity. Although fingerprints and properties are generally used as descriptors, neither is perfect for these purposes. A fingerprint can distinguish between molecules, whereas a property may not do the same in certain cases, and vice versa. When the number of the training set is especially small, the construction of good predictive models is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 90 publications
(76 citation statements)
references
References 30 publications
0
76
0
Order By: Relevance
“…In the absence of extensive HLA-related chemogenomics data in the public domain, the development of virtual screening models that can accurately forecast drug-HLA interactions is extremely difficult. As we noted in our proof - of - concept study [ 44 ], there appears to be an inconsistent application of the molecular docking methodology when studying HLA systems. Indeed, the literature tends to be rather scarce regarding the pre-processing of HLA protein variants prior to modeling as well as which considerations (if any) were made with regards to the co-binding peptide and its ability to stabilize the bound drug.…”
Section: Introductionmentioning
confidence: 97%
See 4 more Smart Citations
“…In the absence of extensive HLA-related chemogenomics data in the public domain, the development of virtual screening models that can accurately forecast drug-HLA interactions is extremely difficult. As we noted in our proof - of - concept study [ 44 ], there appears to be an inconsistent application of the molecular docking methodology when studying HLA systems. Indeed, the literature tends to be rather scarce regarding the pre-processing of HLA protein variants prior to modeling as well as which considerations (if any) were made with regards to the co-binding peptide and its ability to stabilize the bound drug.…”
Section: Introductionmentioning
confidence: 97%
“…In our recent study [ 44 ], we explored the complex intermolecular interactions between the binding pocket of HLA-B*57:01, the co-binding drug abacavir, and three co-binding peptides from the three available X-ray crystals (PDB: 3VRI, 3VRJ, 3UPR) by Illing et al [ 15 ] and Ostrov et al [ 16 ]. After conducting structural alignments of the individual components of our system (HLA-B*57:01 peptide binding pocket, bound abacavir, and co-binding peptide), we concluded that the most significant differences between binding pocket, abacavir, and peptide occurred from the peptide amino acid sequence [ 44 ]. Performing a peptide backbone alignment revealed that the 3D-structure of the peptide backbone was highly conserved [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations